Effects of different cooking methods on volatile flavor compounds of chicken breast. Issue 8 (12th July 2021) - Bi, Jicai; Lin, Zeyuan; Li, Yang; Chen, Fusheng; Liu, Sixin; Li, Congfa
Abstract: Chicken is one of the highest selling meats worldwide. Different cooking methods produce various flavor compounds in cooked chicken, which affect consumers' food choices. In this study, the volatile flavor components of Gushi chicken breast after stewing and air frying were detected using gas chromatography‐ion mobility chromatography (GC‐IMS) and principal component analysis (PCA), and the relative odor activity value (ROAV) was determined using PCA. A total of 43 volatile substances were identified. 3‐(methylthio)propionaldehyde‐M and benzene acetaldehyde can be used as characteristic flavor markers in the air‐fried chicken breast.ethyl acetate, (E)‐2‐octenal‐D, and 2‐ethyl‐1‐hexanol‐D can be used as characteristic flavor markers in the stewed chicken breast. Because these five substances have the most obvious contrast in the fingerprint. The following part describes the specific substances that have mainly contributed to the flavor system in the volatile system obtained by different cooking methods. Finally, the main flavor compounds of the stewed chicken breast were 3‐methylbutanal‐D, octanal‐D, (E)‐2‐nonenal, and other 11 types of compounds (ROAV ≥1). Nine types of compounds (ROAV ≥1), including 3‐methylbutanal‐D, (E)‐2‐nonenal‐M octanal‐M, and hexanal‐M, were the main compounds to characterize the air‐fried chicken breast. Practical applications: GC‐IMS technology combined with the principal component analysis of ROAV can be used to rapidly identify the main flavor substances and the flavor substances having an important role in modifying the overall taste of the sample. It plays a considerably important role in the aroma recombination of substances and can play a role in food processing. Abstract : First, 3‐(methylthio)propionaldehyde‐M and benzene acetaldehyde only appeared in the air‐fried chicken breast, and ethyl acetate, (E)‐2‐octenal‐D, and 2‐ethyl‐1‐hexanol‐D only appeared in the stewed chicken breast. Second, the main flavour compounds of the stewed chicken breast were 3‐methylbutanal‐D, octanal‐D, (E)‐2‐nonenal, and other 11 types of compounds (ROAV ≥1). Finally, nine types of compounds (ROAV ≥1), including 3‐methylbutanal‐D, (E)‐2‐nonenal‐M octanal‐M, and hexanal‐M, were the main compounds to characterise the air‐fried chicken breast.